Expression of functionally active sialylated human erythropoietin in plants - Jez, Jakub (WILEY-VCH Verlag, 2013)
Recombinant human erythropoietin (rhEPO), a glycohormone, is one of the leading biopharmaceutical products. The production of rhEPO is currently restricted to mammalian cell expression systems because of rhEPO's highly complex glycosylation pattern, which is a major determinant for drug-efficacy. Here we evaluate the ability of plants to produce different glycoforms of rhEPO. cDNA constructs were delivered to Nicotiana benthamiana (N. benthamiana) and transiently expressed by a viral based expression system. Expression levels up to 85 mg rhEPO/kg fresh leaf material were achieved. Moreover, co-expression of rhEPO with six mammalian genes required for in planta protein sialylation resulted in the synthesis of rhEPO decorated mainly with bisialylated N-glycans (NaNa), the most abundant glycoform of circulating hEPO in patients with anemia. A newly established peptide tag (ELDKWA) fused to hEPO was particularly well-suited for purification of the recombinant hormone based on immunoaffinity. Subsequent lectin chromatography allowed enrichment of exclusively sialylated rhEPO. All plant-derived glycoforms exhibited high biological activity as determined by a cell-based receptor-binding assay. The generation of rhEPO carrying largely homogeneous glycosylation profiles (GnGnXF, GnGn, and NaNa) will facilitate further investigation of functionalities with potential implications for medical applications.